Relação entre o desenvolvimento dos ovários e atividade dos Corpora Allata de operárias de Frieseomelitta silvestri languida (Hymenoptera, Apidae) - Cunha, Marina A. Staurengo da [UNESP]; Cunha, Rubens Alves da [UNESP]; Pimentel, Marcia A. de Lima [UNESP] (Sociedade Brasileira de Zoologia, 1989)
In the absence of the queen, a few workers of F. s. languida developed their ovaries forming nevertheless, only one follicle with a single oocyte which was unable to form yolk spheres. They never showed signals of degeneration or resorption. The corpora allata were homogeneous during all the 5 months of orphanage studied. Its activity might be low but constant, able to maintain the follicle entire, but unable to promote the yolk spheres assembly.
Interaction between ovarian development and Corpora Allata activity in Frieseomelitta silvestri languida workers (Hymenoptera, Apidae)